Enhanced phytoremediation of metal contaminated soils aimed at decreasing the risk of antibiotic resistance dissemination - Garbisu, Carlos; Alkorta, Itziar (Frontiers in Environmental Science, 2024)
The enhanced phytoremediation of metal contaminated soils holds great promise for the recovery of soil health and functionality, while providing a range of co-benefits, from an environmental and human health perspective, derived from the revegetation of the degraded sites and the concomitant delivery of ecosystem services. Due to diverse evolutionary co-selection mechanisms between metal resistance and antibiotic resistance in bacteria, metal contaminated soils are considered potential reservoirs of antibiotic resistant bacteria (ARB) which can contribute to the existing antibiotic resistance crisis. During the enhanced phytoremediation of metal contaminated soils, the application of organic wastes (e.g., manure, slurry, sewage sludge) as soil amendments can aggravate the risk of antibiotic resistance spread, because they often contain ARB which harbor antibiotic resistance genes (ARGs) that can then be propagated among soil bacterial populations through horizontal gene transfer (HGT). Due to the magnitude and criticality of the antibiotic resistance crisis, as well as the higher risk of spread and dispersal of ARB and ARGs (they make copies of themselves) compared to metals, it is proposed here to aim enhanced phytoremediation strategies towards decreasing the soil resistome (and, hence, the risk of its potential link with the human resistome), while reducing total and/or bioavailable metal concentrations and restoring soil health and the delivery of ecosystem services. To this purpose, a decalogue of practices is tentatively suggested. Finally, a proper management of plant and soil microbial compositions is a most crucial aspect, together with the selection of the right organic wastes and phytoremediation practices.